Effect of Kangshuanyihao Formula on the Inflammatory Reaction and SIRT1/TLR4/NF-κB Signaling Pathway in Endothelial Injury. (30th April 2017) - Han, Jie; Tong, Hua-Qin; Cheng, Song-Yi; Yang, Li; Chen, Han-Yu; Chen, Jian-Dong; Chen, Xiao-Hu
Abstract : Endothelial injury plays an important role in atherosclerosis (AS). Kangshuanyihao formula uses therapeutic principles from Chinese medicine to supplement Qi, thereby promoting blood circulation, and remove blood stasis. The mechanism by which the formula inhibits endothelial injury was examined in a rat model of 1, 25-dihydroxyvitamin D3 (VD3 ) intraperitoneal injection and high-fat-induced endothelial injury. Rats were randomly divided into the model, high-dose, middle-dose, low-dose, positive drug (rosuvastatin), and combination (positive drug + middle-dose) groups; 10 Sprague-Dawley rats served as the blank group. The aortic endothelium was stained with hematoxylin and eosin and the levels of blood lipids and inflammation markers (mRNA and protein) were measured. Endothelial injury, lipid levels, and inflammation were increased in the model. Kangshuanyihao formula reduced endothelial injury, improved lipid levels, and downregulated inflammation, as shown by significant reduction of the protein levels of SIRT1, TLR4, and NF- κ B and mRNA levels of SIRT1, TLR4, NF- κ B, IL-1 β, IL-6, and IL-12. Thus, we conclude that Kangshuanyihao formula can inhibit the inflammatory reaction in the rat model of high-fat-induced endothelial injury after intraperitoneal injection of VD3 . This mechanism may be attributed to regulating the SIRT1/TLR4/NF- κ B signaling pathway.